2021
DOI: 10.3390/microorganisms9020353
|View full text |Cite
|
Sign up to set email alerts
|

Gut–Skin Axis: Current Knowledge of the Interrelationship between Microbial Dysbiosis and Skin Conditions

Abstract: The microbiome plays an important role in a wide variety of skin disorders. Not only is the skin microbiome altered, but also surprisingly many skin diseases are accompanied by an altered gut microbiome. The microbiome is a key regulator for the immune system, as it aims to maintain homeostasis by communicating with tissues and organs in a bidirectional manner. Hence, dysbiosis in the skin and/or gut microbiome is associated with an altered immune response, promoting the development of skin diseases, such as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
230
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(303 citation statements)
references
References 357 publications
(366 reference statements)
2
230
0
4
Order By: Relevance
“…Acne is a chronic skin disease, affecting the pilosebaceous units, with multifactorial pathogenesis including hormonal influence, the immunological state of the host, diet, deregulation of insulin-like growth factor, excessive sebum production and FoxO1 deficiency [152,153]. Considering the pathogenesis of acne, Cutibacterium acnes has been implicated as an important pathogenic factor.…”
Section: Acnementioning
confidence: 99%
“…Acne is a chronic skin disease, affecting the pilosebaceous units, with multifactorial pathogenesis including hormonal influence, the immunological state of the host, diet, deregulation of insulin-like growth factor, excessive sebum production and FoxO1 deficiency [152,153]. Considering the pathogenesis of acne, Cutibacterium acnes has been implicated as an important pathogenic factor.…”
Section: Acnementioning
confidence: 99%
“…While the three tissues affected in these studiesjoint, eye, and kidneys-are not heavily-colonized by microbes, we examined the connection between the intestinal tract and skin, which both harbor large and diverse microbial communities capable of influencing host immunity. The concept of linked gut and skin dysbiosis has been a topic of conjecture as relates to disease pathogenesis (De Pessemier et al 2021;O'Neill et al, 2016;Salem et al, 2018). However, the few studies that have tackled the mechanistic connection between immunity at these two barrier sites have focused on anaphylaxis and allergy (Leyva-Castillo et al 2019, Oyoshi et al 2011, Rigoni et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Just as there is communication between the human cells, bacteria also communicate between the different niches where they are established [ 118 ], as well as with the human cells [ 119 , 120 ]. As expected, since its harbors the vast majority of the microorganisms, the gut microbiota is the main core of communication, and it seems plausible that the main interplay is established between gut microbiota and the others through the well-described gut-liver axis [ 121 ], gut–brain axis [ 122 ], gut–skin axis [ 123 ], and oral–gut axis [ 124 ]. On the other hand, other authors have shown crosstalk between different regions in which the gut microbiota is not involved, such as the oral–pulmonary axis [ 69 ].…”
Section: The Interplay Between the Different Microbiotasmentioning
confidence: 99%